Frequency of pregnancy complications among women diagnosed with COVID-19 during pregnancy, treated at Hospital General Regional con Medicina Familiar N.° 1 in Cuernavaca, Morelos, between March 2020 and March 2022 - Rojas Campos, Efraín (2025)
Objective: To identify the most frequent pregnancy complications among women diagnosed with COVID-19 during pregnancy between March 2020 and March 2022. Materials and methods: This descriptive, cross-sectional study was based on a review of 100 medical records of pregnant women diagnosed with COVID-19 who received care between March 2020 and March 2022. A structured questionnaire was used to collect data on variables of interest, including sociodemographic characteristics, clinical information, obstetric and gynecologic history, and pregnancy complications. A univariate analysis was conducted using measures of central tendency, frequencies and percentages, with the support of Stata 13. Results: Among the sample, 47 % were in the 31–40 age group, 86 % had a partner, 57 % were salaried employees and 73 % had basic education. While 54 % of the women experienced no complications, 46 % developed complications, including moderate preterm delivery (15 %) and premature rupture of membranes (6 %). An elective cesarean section recommended by an obstetrician was the delivery method for 39 % of the women. In terms of pregnancy history, 25 % had previously given birth, 11 % had experienced a miscarriage, 25 % had undergone a cesarean section and 1 % had a history of ectopic pregnancy. Conclusions: This study is clinically relevant due to the limited data available on this topic in our country and the broader global impact of maternal mortality. Notably, nearly 50 % of the patients had a body mass index (BMI) consisting with overweight—an established risk factor for complications. Regarding gestational age at diagnosis, 67 % were in their third trimester. Mild symptoms were the most frequently reported (73 %), and type 2 diabetes mellitus was one of the associated comorbidities observed. One patient (1 %) died from severe COVID-19. This impacts national development by causing negative outcomes such as increased child morbidity and mortality, school dropouts and family breakdown.